From paper to pixels: transforming financial practices in community qur’anic early childhood education - Agustina, Yumniati; Nurcahyo, Widyat; Ningsih, Sri Setia (Lebah, 2025)
This community engagement initiative, conducted as a collaboration program of several lecturers from various universities, aimed to strengthen the financial management capacities of Taman Pendidikan Al-Qur’an (TPA) Sufaini, a grassroots religious education center in Ciputat, South Tangerang. The institution, which offers free Qur’anic instruction to underprivileged children, faced persistent challenges in maintaining accurate and transparent financial records due to the absence of standardized accounting practices and limited technological literacy among its administrators. In response, a structured training program was designed and implemented to provide foundational knowledge of accounting principles and to introduce mobile-based digital bookkeeping tools that could be directly integrated into the institution’s daily operations. The methodology of the program emphasized participatory learning, contextualized instruction, and hands-on practice using actual institutional data. Evaluation was conducted through qualitative methods such as observation and dialogue. Approximately 85% of participants demonstrated significant improvements in preparing standardized financial reports and greater awareness of transparency and accountability. The outcomes revealed both the potential and limitations of digital financial literacy interventions in low-resource educational settings. While the training effectively introduced essential skills, sustainability remains contingent on continued support, institutional commitment, and access to adequate technology. This initiative contributes to broader discourses on community-based capacity building and highlights the role of higher education institutions in facilitating inclusive development through practical, needs-driven knowledge transfer. The experience at TPA Sufaini serves as a model for replicable interventions in similar contexts, with implications for scaling and long-term policy integration within informal education systems.